Kepastian Hukum Bagi Kreditur Sehubungan Pelaksanaan Eksekusi Jaminan Fidusia Pasca Putusan Mahkamah Konstitusi Nomor 18/PUU-XVII/2019 Yang Berdampak Kerugian Finansial - Puspitasari, Dessy; Sahril, Iran; Nesseri, Jelly (Universitas Muhammadiyah Kotabumi, 2024)
The Constitutional Court Decision Number 18/PUU-XVII/2019 has brought changes to the execution process in fiduciary guarantees, making the creditor's position change before the birth of the decision. The existence of requirements for creditors in executing fiduciary security objects and determining defaults has changed, resulting in creditors not being able to immediately execute fiduciary security objects. This raises issues related to the certainty of the creditor's right to execute the fiduciary security object.The formulation of the problem in this research is how the Legal Consequences for Creditor Regarding the Implementation of Fiduciary Guarantee Execution After the Decision of the Constitutional Court Number 18/PUU-XVII/2019 Which Affects Loss Constitutional Court Decision Number 18 / PUU-XVII / 2019 Which Impacts Financial Losses and how Legal Certainty for Creditors in Connection with the Execution of Fiduciary Guarantees Financial Losses and how is Legal Certainty for Creditors in Connection with Implementation of Fiduciary Guarantee Execution After the Constitutional Court Decision Number 18/PUU-XVII/2019 Which Impacts Financial Losses. Theories used Legal Effect Theory and Legal Certainty Theory are used.